Strategi Pemasaran Buah Naga dengan Pemanfaatan Media Sosial di Kecamatan Jawai, Kabupaten Sambas, Kalimantan Barat - Laila Nuzuliyah; Darma Irawan (Balai Pelatihan Pertanian Jambi, 2022)
The increasing number of dragon fruit cultivation both within the region and outside the region will increase production yields so that an efficient distribution channel is needed. This study aimed to understand the digital marketing of dragon fruit commodities. The study used a qualitative descriptive method through data collection techniques with in-depth interviews about dragon fruit digital marketing strategies based on marketing mix indicators. The data analysis method used SWOT analysis to identify internal and external elements method to develop priority strategies. The results of the study using SWOT analysis showed that the position is located at the point (1,310; 0,086) or in quadrant 1, namely an aggressive strategy with the IFAS calculation is 2,586, and the EFAS calculation is 3,061. Determining of strategic priorities using the AHP method produces an alternative priority strategy, namely innovating with an attractive and up to date sales display, which results in a weight of 0,497. Conducting training and education related to digital marketing is the second priority which results in a weight of 0,242. These two strategies are a combination of choices to support the dragon fruit digital marketing strategy to increase sales volume. Based on this, farmers need to innovate that their sales display is attractive and up to date, such as adding a digital platform that is used by designing information so that the promotion display is more attractive